Evaluation of pro-inflammatory cytokines in nutritionally stunted Egyptian children - Awatif M. Abd El-Maksoud; Sahar A. Khairy; Hayat M. Sharada; Mohga S. Abdalla; Nehal F. Ahmed (SpringerOpen, 2017)
Objectives: Stunting affects 32% of children living in developing countries and has a major impact on child health and development. In this study, we aimed to assess the pro-inflammatory cytokines and some micronutrients among the healthy control and nutritionally stunted Egyptian children. Subjects and methods: A total of 88 children were enrolled; 60 stunted children and 28 non-stunted of matched age and sex. Clinical, demographic characteristics, serum levels of calcium, magnesium, and zinc were measured. Plasma levels of interleukin-6 (IL-6), tumor necrosis factor alpha (TNFα) and C - reactive protein (CRP) were measured in these subjects. Results: Stunted children showed a marked decrease in weight and weight-for-age Z score (WAZ) versus healthy one. Significant reduction in the serum level of Ca, Mg, and Zn was detected in stunted children compared to those of the healthy control subjects. Moreover, the mean serum levels of IL-6 (pg/ml) (1.5 Vs 1.6), TNFα (pg/ml) (1.7 Vs 1.8) and CRP (mg/l) (0.7 Vs 1) were significantly higher among the stunted group compared to control. Conclusion: Nutritionally stunted Egyptian children have lowered serum levels of Zn. Ca, and Mg, in addition to elevated serum levels of proinflammatory cytokines (Il-6, TNFα, and CRP).